Implementasi K-Means Dalam Pengelompokan Penyebaran COVID-19 di Jawa Barat - Muhammad Wildan Goni; Dudih Gustian; Falentino Sembiring (Progresif: Jurnal Ilmiah Komputer, 2021)
AbstractConfirmed cases of the COVID-19 virus that are still unstable, as well as the comparison of total confirmed and total recoveries are quite far, which if not treated quickly will cause the number of people exposed to be increasing. This article aims to test the K-Means algorithm in grouping the spread of Covid-19 in West Java. The grouping was carried out based on confirmed parameters, isolated/under treatment, completed isolation/recovered and died from each area in West Java Province. K-means performs clustering in 3 clusters, namely the high distribution cluster (C1), the moderately distributed cluster (C2) and the lightly distributed cluster (C3). Based on the results of system analysis and testing, there are 2 regions in the high distribution cluster (C1), 6 regions for the medium distribution cluster (C2), and 19 regions for the low distribution cluster (C3).Keywords: Spread of COVID-19, K-Means Algorithm, Grouping AbstrakKasus terkonfirmasi virus COVID-19 yang masih belum stabil, serta perbandingan total terkonfirmasi dan total sembuh cukup jauh, dimana jika tidak segera ditangani dengan cepat akan menyebabkan jumlah orang yang terpapar menjadi semakin banyak. Artikel ini bertujuan untuk menguji algoritma K-Means dalam pengelompokan penyebaran Covid-19 di Jawa Barat. Pengelompokkan dilakukan berdasarkan parameter terkonfirmasi, isolasi/dalam perawatan, selesai isolasi/sembuh dan meninggal dari masing-masing daerah yang ada di Provinsi Jawa barat. K-means melakukan klasterisasi dalam 3 cluster yaitu cluster penyebaran tinggi (C1), cluster penyebaran sedang (C2) dan cluster penyebaran ringan (C3). Berdasarkan hasil analisis dan pengujian sistem, daerah yang masuk ke cluster penyebaran tinggi (C1) sebanyak 2 daerah, untuk cluster penyebaran sedang (C2) sebanyak 6 daerah, dan cluster penyebaran rendah (C3) sebanyak 19 daerah.Kata kunci: Penyebaran COVID-19, Algoritma K-Means, Pengelompokan